INTEGRATED MARKETING COMMUNICATION STRATEGY AND VISIT INTENTION THE CASE OF ARUNA DINE AND COFFEE (The Indonesian Journal of Business Administration, 2019)
IMC believed will increase the revenue of a company, The research will focus on the integrated marketing communication and how to improve the marketing communication for Aruna dine and coffee and to find the best solution in integrated marketing communication so Aruna dine and coffee can compete for the competition at the cafe and coffee shop, the typical of IMC that used is advertising, direct marketing, personal selling, and sales promotion with this research it will improve the Visit Intention to a coffee shop.Keywords:IMC, Integrated Marketing Communication, Advertising, Direct Marketing, Sales Promotion, Personal Selling, Visit Intention, Cafe, Coffee Shop.